The land scale and Its connection with production systems of the area of Catriló, La Pampa (Semiárida, 2020)
The Argentinean economic policy which predominated in the 90s caused significant changes in the agricultural sector. In that context, farmers from the department of Catriló (La Pampa) experienced important heterogeniety accoding to their different characteristics. The overall objective of this study consisted of dealing with a study on the main characteristics of farmers from Catriló. Besides, the study aimed not only at establishing the relation between different variables, such as the predial scale, training, time devoted to management, diversity of production, but also at stratifying farmers in case of proving that there is some heterogeneity among them. To this end, descriptive statistical study and the Chi Square method were used. Due to the existence of significant heterogeneity, farmers were split into three groups according to their stratification. From the three groups, the group of greater scale and greater business capacity stands out because of the strategies they use and the resources which enable them to experience less vulnerability than the other groups. The regional agriculture and livestock sector was characterized as presenting less quantity of fields with greater farm size, with predominance of livestock farming in the systems of lesser scale and increasing "mining" agriculture in the systems of greater scale. In this way, a short term rentability model which is more flexible but less sustainable regarding the social and environmental aspect is consolidated. Each farmer's group characterization will enable us to design policies which not only take into account the restrictions that the most vulnerable regional systems face but also tend to minimize the impact of the predominant model.